Developing Curriculum for Deep Thinking The Knowledge Revival - Surma, Tim.; Vanhees, Claudio; Wils, Michiel; Nijlunsing, Jasper; Crato, Nuno.; Hattie, John.; Muijs, Daniel; Rata, Elizabeth; Wiliam, Dylan; Kirschner, Paul A.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book discusses why the seemingly straightforward strategy of teaching children how to think deeply does not work and offers an alternative way forward for the curriculum to achieve these objectives. Over the years, the role of knowledge in the curriculum has, like a pendulum, shifted between two extremes, from highly visible to virtually invisible knowledge elements. Insights from cognitive and educational psychology, sociology, and curriculum studies are used to underpin the current knowledge revival that is widely being observed in education. A knowledge-rich curriculum is proposed by the authors as not only the soundest way forward to both effectively acquire knowledge and complex cognitive skills in school, but also as a crucial lever to achieve equitable opportunities for all students. In understanding how a knowledge-rich curriculum can enhance learning, three overarching principles are discussed: (1) content-richness, (2) coherence, and (3) clarity. These principles are illustrated through practical examples from schools and educators who have effectively integrated knowledge-rich curricula.
1.Introduction -- 2.How knowledge matters -- 3.Knowledge matters: a learning perspective -- 4.Knowledge matters: a sociological perspective -- 5.Knowledge matters: a democratic perspective -- 6.Knowledge and the curriculum -- 7.Everything starts with the curriculum -- 8.Curriculum as a pendulum -- 9.Towards the best of both worlds: a knowledge-rich curriculum -- 10.On Content-richness -- 11.On Coherence -- 12.On Clarity -- 13.What are the effects of a knowledge-rich curriculum -- 14.Concluding remarks -- 15.Executive summary -- 16. References.
Keywords: Teachers -- Training of; Study Skills; Education -- Curricula; Teaching and Teacher Education; Study and Learning Skills; Curriculum Studies